Comparative study on changes in Cd accumulation and ionome between rice and spinach: Impact of zinc ion activity. Issue 1 (29th November 2022) - Wang, Meie; Ma, Wankai; Chaney, Rufus L.; Green, Carrie E.; Chen, Weiping
Abstract: Excessive Cd accumulation in rice grain has caused chronic Cd diseases in humans. In most crops, 100 times more Zn than Cd strongly inhibits Cd uptake and translocation. However, this response is not found for rice ( Oryza sativa L.), which was found to have an unusual Cd uptake pattern compared with other crops, such as spinach ( Spinacia oleracea L.). Moreover, studies on shared transporters between Zn and Cd using normal solution experiments with traditional high concentrations of metal ions may result in irrelevant interactions. Therefore, we developed ethyleneglycoltetraacetate‐buffered nutrient solutions in this work. Rice and spinach seedlings were grown under calibrated low Cd 2+ activity and low to phytotoxic Zn 2+ activity levels while buffering other micronutrient cations at sufficient levels. Results showed that as rice grew with pZn 2+ = 8.1–5.4, root Cd and shoot Ni decreased significantly and gradually. However, shoot Cd and Mn in rice decreased slightly with the increase of solution Zn 2+ from deficiency to sufficiency and then increased at toxic Zn 2+ solution (pZn 2+ = 5.4). The shoot/root ratios of Cd in rice under toxic pZn 2+ (5.6 and 5.4 pZn 2+ activity) were significantly increased ( p < .05). It could be concluded that rice absorption of Cd is not inhibited by co‐contaminating (toxic) Zn. For spinach, with Zn varying from pZn 2+ = 8.1–5.7, both shoot and root Cd substantially decreased, as did shoot Ni. This work revealed that, to understand food chain Cd risks, one needs to consider the inhibitory role of Zn in limiting Cd absorption in all crops studied except rice. Core Ideas: Shoot Cd and Mn in rice were the lowest under sufficient external Zn 2+ . Shoot Cd and Mn in rice were elevated under toxic external Zn 2+ . Both shoot and root Cd and Mn in spinach decreased with increasing external Zn 2+ . Shoot Ni in both rice and spinach decreased with increasing external Zn 2+ .